Inovasi Pelayanan dalam Pengelolaan Sampah: Studi pada Bank Sampah - Danar, Oscar Radyan; Rohmasari, Amin; Novita, Asti Amelia (Jurnal Ilmiah Administrasi Publik, 2019)
The purpose of this study is to conduct an analysis of public service innovation in waste management in the city of Malang through the Malang Garbage Bank (BSM). In 2015 BSM get an award at the public service innovation system competition (SINOVIK). BSM won the top 25 public service innovations and became a national pilot conducted by the Ministry of Environment and Forestry (KLHK). This research using innovation and waste management theory. A qualitative approach through interviews and secondary data through various documents is the method of this research. The results of this study indicate that the process of managing waste by BSM through the process of sorting waste by customers, taking or depositing waste, sorting waste by BSM and managing waste becomes plastic chopped. Waste management by BSM able to change the mindset of the people who initially assumed that waste is an item that is no longer have economic value. Waste management innovation includes the type of process innovation, service method innovation, strategy or policy innovation, and system innovation. BSM is in the level of transformative innovation and discontinues innovation category.